Koncepcja zmodyfikowanej strategicznej karty wyników - Cyfert, Szymon (Modified balanced scorecard concept, 2005)
The aim of this article is to analyze limitations of the Balanced Scorecard methodology from the perspective of the process management, and on this base, to define directions of changes in the Balanced Scorecard. The article starts with a general discussion of limitation of the Balanced Scorecard system from the process management perspective, and description of consequences of those dysfunctions. This helps to describe five directions of change are laid down to ensure integration of the Balanced Scorecard with the process management system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 406-412